The Relationship between Hyperuricemia and Hypertension in Internal Medicine Policlinic Patients in RSUD Dr. Soetomo 2019-2021 - Mahindisyah, Muhammad Ghifary; Humairah, Ira; Tjempakasari, Artaria; Herawati, Lilik (Formosa Journal of Science and Technology, 2024)
Hypertension was characterized by persistently high blood pressure in the systemic arteries.  This typed of researched was descriptive retrospective with consecutive sampling used inclusion and exclusion criteria. Data analysis used the Skewness and Kurtosis Normality Test and Chi Square Test with p<0,05.  The results of the studied showed that 42 people was found with a population percentage of 67,7% who was known to had hyperuricemia with hypertension. There was a significant relationship between the incidence of hyperuricemia and the incidence of hypertension with a valued of p=0,003 (p<0,05).  The odds ratio (OR) valued in this study was 8,17, meaning that patients with hyperuricemia had an 8,17 times greater chance of suffering from hypertension compared to patients without hyperuricemia. It was recommended that further research use case control studies or cohort studies to find out which variables are the cause and effect between hyperuricemia and hypertension.